The Positivity Scale: Concurrent and Factorial Validity Across Late Childhood and Early Adolescence - Zuffianò, Antonio; López-Pérez, Belén; Cirimele, Flavia; Kvapilová, Jana; Caprara, Gian Vittorio (Frontiers in Psychology, 2019)
Despite the well-established protective functions of positivity (i.e., a dispositional self-evaluative tendency to view oneself, life, and future under a positive outlook) from middle adolescence to old age, its reliable assessment and contribution to a proper psychological functioning have received little attention during previous developmental phases. In this article, we aimed to evaluate the psychometric properties and construct validity of the eight-item Positivity Scale (P Scale; Caprara et al., 2012) during late childhood and early adolescence in a sample of British students (N = 742; 48% boys) from both primary (Mage = 10.75, SD =.52) and secondary schools (Mage = 13.38 years, SD = .94). First, results from confirmatory factor analysis (CFA) attested to the plausibility of the hypothesized 1-factor structure of the P Scale in a revised CFA model including the correlation between the residuals of two items similar in their wording. Next, we found evidence for strong (scalar) measurement invariance of the P Scale across late childhood and early adolescence as well as for its concurrent validity as indicated by expected relations of positivity to indicators of adjustment (i.e., prosocial behavior) and maladjustment (i.e., externalizing and internalizing problems). Overall, these findings support the concurrent and factorial validity of the P Scale as a short self-report instrument to measure children’s tendency to view their experience from a positive stance. We discuss the implications of our results for improving the wording of the items composing P Scale as well as for understanding the dispositional mechanisms conducive to psychological health and wellbeing across late childhood and early adolescence.